A case study on the influence of selected parameters on microexplosion behavior of water in biodiesel emulsion droplets - Khan, M.Y. (American Society of Mechanical Engineers (ASME), 2017)
Microexplosion behavior of water in biodiesel emulsion droplets was studied by suspending a single droplet on a wire type thermocouple. Water in biodiesel emulsion droplets with 9, 12, 15, and 18 water by volume was observed in the Leiden frost regime using a hot plate as the heat source maintained at two different temperatures of 400°C and 500°C. The evolution of microexplosion was recorded with a high-speed camera synchronized with a temperature data logger. The emulsions were prepared by an electrical stirrer fitted with customized made blades rotating at 1500 rpm for 15 min. The emulsions were stabilized with two different hydrophilic-lipophilic balance (HLB) values, which were prepared by mixing two different commercial surfactants. It is found that the microexplosion time and temperature were influenced by emulsion stability, water content, surfactant dosage, base plate temperature, and HLB value. All the unstable emulsions developed microexplosion at both plate temperatures. Emulsions stabilized with an HLB value of 6.31 and 18 water content did exhibit microexplosion at both base plate temperatures. Also, the waiting time was found to decrease with increasing surfactant concentrations for a 500°C plate temperature compared to 400°C. Copyright © 2017 by ASME.